2016
DOI: 10.1111/1758-5899.12367
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Individuals in a Globalized World

Abstract: Mark Zuckerberg, founder and CEO of Facebook, made media headlines at the end of last year when he announced his intention to donate most of his Facebook shares to charity. This article deals with the significance and potential of individuals, such as Zuckerberg, in a globalized world, to determine global policy agendas. Philanthropists who head global foundations are the most apparent. While philanthropists' involvement in international relations is based on their capital, celebrities increasingly use their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For example, these contradictions come into even sharper focus through the actions of celebrity green entrepreneurs like Richard Branson (Prudham, 2009). Partzsch (2016) observes that, in the past two decades, power has shifted from state actors towards philanthropists, celebrities, and social entrepreneurs, creating problems for democratic accountability and legitimacy. Anderson (2011) offers a more ambivalent account of the situation through her critical review of media coverage of climate/environmental issues and the potential role of celebrities in moving the broader public to action.…”
Section: Discussionmentioning
confidence: 99%
“…For example, these contradictions come into even sharper focus through the actions of celebrity green entrepreneurs like Richard Branson (Prudham, 2009). Partzsch (2016) observes that, in the past two decades, power has shifted from state actors towards philanthropists, celebrities, and social entrepreneurs, creating problems for democratic accountability and legitimacy. Anderson (2011) offers a more ambivalent account of the situation through her critical review of media coverage of climate/environmental issues and the potential role of celebrities in moving the broader public to action.…”
Section: Discussionmentioning
confidence: 99%
“…These two models are made because the actors, resources, scale, strategy and entrepreneurial processes of these two models are different, but both shares the same tangent point in the context of sustainability and identity formation through the development of independence, albeit employing different strategies. The next equation lies in the ideology or moral philosophy of its entrepreneurial initiator (the "great man" school) [22]. On the other hand, the two cases we studied involve revolutionary system changes, thus traditionally belonging to Social Engineering typology.…”
Section: Social Engineeringmentioning
confidence: 99%
“…This naming refers to the emergence of individual or collective actors who play an entrepreneurial function at the community level as well as global. As theorized by [22], "due to globalization and the increase of private authority, some individuals with a transformational orientation have now obtained new resources of power that allow for the novel non-state and non-collective agency." Therefore she suggests three categories of individual agents increasingly relevant to global governance: i.e.…”
Section: Social Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In these collaborative processes an important role is assigned to agency (Harting et al., ; Huitema and Meijerink, ; McNamara, ; Meijerink and Stiller, ; Termeer and Bruinsma, ). Studies have shown that exploring global policy dynamics from a micro agency‐centered perspective sheds light on the crucial role of actors in the dynamics through which constellations like GACSA get operationalized (Braithwaite and Drahos, ; Partzsch, ). Such a micro perspective allows us to understand how actor's activities are influenced by contextual developments, and how these activities in turn transform or reproduce macro‐level patterns in the policy process (Torfing, ) thereby increasing insight in the mechanisms underlying policy development.…”
mentioning
confidence: 99%